The Influence of Waqf Productivity on Education in The Province of Yogyakarta Special Region (DIY) - Mochamad Mansur; Tatik Mariyanti (BPJP - STEI, 2022)
This study explores the influence of Nazhir competence in waqf management on education, with waqf productivity as an intervening variable. The study aims to contribute to the existing knowledge on the relationship among Nazhir competence, waqf management, productivity, and education. The urgency of the study stems from the need to generate valuable insights and knowledge about the impact of Nazhir competence and waqf management on education, with productivity as an intervening variable. Data for the study were collected using the Structural Equation Modeling (SEM) method with the LISREL 8.80 software, from a population of 500, and a sample of 356 was selected. The study highlights the crucial role of productive waqf management in optimizing the contribution of waqf to the education sector, from basic to higher education, considering the persisting concerns about the quality of education in Indonesia. The cost of continuing education and the challenge of enhancing experiences make it difficult for individuals in the middle to low economic groups to access education. The study findings indicate that Nazhir competence does not significantly influence waqf productivity, while management of waqf significantly impacts productivity. Moreover, some aspects of Nazhir competence are not significantly related to education, while waqf management significantly influences education. Finally, productivity as an intervening variable does not significantly impact education. These results imply that there is a need for education and training programs to enhance Nazhir competence in waqf management, particularly given the crucial role of productive waqf management in supporting quality education and the economic welfare of Muslim communities. Institutions and community organizations responsible for waqf management should provide socialization programs to promote professionalism, accountability, and good governance, leading to optimal results.